THE BLUE ALIEN IN KOI MIL GAYA FILM: POPULAR LITERATURE - Luluk Hanikmah (English Teaching Journal : A Journal of English Literature, Language and Education, 2016)
The purpose of this research is to describe the blue alien as the phenomenon Alien’s representation in science fiction of Bollywood and Bollywood’s action in bringing outer space alien to Indian culture that is represented in Koi Mil Gaya film. This research uses qualitative research. The researcher needs popular literature by Ida Rochani Adi to get what the author is willing to share her readers. It is also a way to the researcher to investigate why the author choose alien as the new character, and is there popular culture inside the character evidences the effects and goals of the author in creating a story. The analysis reveals that the alien’s representation of Bollywood’s science fiction, and Bollywood’s action in bringing outer space alien to India culture. The conclusion shows there are similar formula in each Bollywood science fiction in alien’s representation and Bollywood action in bringing outer space alien to India culture is influenced by 3 factors, there are: Hollywood influence, Ancient India influence, and popular news in India. The researcher uses the symbol to analyze the blue alien as the representation of Lord Krishna. It is Hindu mythology. Hindu mythology is popular culture in India belief. It is appropriate with the researcher’s assumption that the blue alien has correlation with India culture. In conclusion, the alien which has blue skin is the appearance of Lord Krishna.